INTEGRATING TASK- AND GAME-BASED LEARNING INTO AN ONLINE TOEFL PREPARATION COURSE DURING COVID-19 OUTBREAK (Malaysian Journal of Learning and Instruction, 2022)
The COVID-19 epidemic has compelled educational institutions worldwide to implement online learning while maintaining the same level of quality as face-to-face instruction. The majority of universities in Indonesia offer TOEFL preparation classes to undergraduate students, and the outbreak has had an effect on how those courses are delivered. However, there is a dearth of research on the most effective instructional strategies for delivering an online TOEFL preparation course to a large number of students who have no prior experience with online learning. Thus, this study examined the integration of task- and game-based learning into an online TOEFL preparation course taught at two Indonesian institutions over the period of twenty online class meetings totaling 40 class hours. It involved undergraduate students (N = 48) from Politeknik Perkeretaapian Indonesia Madiun's Railway Mechanical Technology study program and Universitas Muhadi Setiabudi's Management study program.